Munkaerő-keresleti előrejelzés vállalati várakozások alapján: Két vállalati adatfelvétel tanulságai - Ágnes Czibik; Mihály Fazekas; Nándor Németh; András Semjén; István János Tóth (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
– Our paper examines the possible role of enterprise surveys in the forecasting of labour market processes. Based on two enterprise surveys with large samples we examine to what extent are enterprises, differing in their size, sales revenues, ownership structure and markets, capable to predict their future labour market demand or manpower requirements for different time horizons. We explore the enterprise characteristics and planning features determining the maximum time horizon and accuracy of the manpower forecasts of enterprises. Both objective and subjective indicators are used in the analysis of the accuracy of forecasts. An empirical study of enterprises' capability to forecast labour market needs and the accuracy of such predictions seems crucial in determining the possibilities and the limits of enterprise surveys in producing forecasts for aggregate manpower needs of the economy or predicting labour demand by vocations and qualifications. We also investigate the ways enterprises perceive the qualitative changes in job contents, and the ways they evaluate the changes in qualification and skill requirements by job categories. Managers' perception of new skill requirements in their own enterprises and in the economy as a whole are also dealt with in the paper.
Keywords: J21; J23; J40; M54; 330; labour demand; business planning; enterprise survey; labour market requirements; change in job content; Arbeitsnachfrage; Prognoseverfahren; Unternehmensplanung